Analisis Semiotika Puisi "Sepantun Laut" Karya J.E Tatengkeng (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This article discusses the semiotic analysis of the poem "Sepantun Laut" by J.E Tatengkeng. Semiotic analysis is an analytical method that examines a sign contained in an object to find out the meaning contained in the object. Semiotics or in Barthes' terms, semiology, basically wants to study how humanity uses things. According to Lechte (in Sobur, 2003, p. 16), Semiotics is a theory about signs and marking. The purpose of semiotic analysis in the poem "Sepantun Laut" by J.E Tatengkeng is to find out the meaning contained in each sign contained in the poem "Sepantun Laut" by J.E Tatengkeng. The discussion in this article relates to the elements of icons, symbols, and indexes as stated by Pierce which will later produce the overall meaning. The poem "Sepantun Laut" means feelings full of hope, sad and mixed feelings.